2017
DOI: 10.3390/ma10121418
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Dichalcogenides for Environmental Chemical Sensing

Abstract: 2D transition metal dichalcogenides are attracting a strong interest following the popularity of graphene and other carbon-based materials. In the field of chemical sensors, they offer some interesting features that could potentially overcome the limitation of graphene and metal oxides, such as the possibility of operating at room temperature. Molybdenum-based dichalcogenides in particular are among the most studied materials, thanks to their facile preparation techniques and promising performances. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 114 publications
(133 reference statements)
2
20
0
2
Order By: Relevance
“…As for graphene and graphene oxide, its morphological characteristics have been exploited for the fabrication of gas sensors. MoS 2 opens the doors to the discovery and isolation of novel 2D nanostructures of sulphides and selenides, like WS 2 , WSe 2 , MoSe 2 and so forth [ 22 , 23 , 24 ]. On the other hand, 2D materials constituted of just one atomic species have been successfully synthesized [ 25 ], like one layer thick black phosphorus (phosphorene) [ 21 , 26 ] or silicon (silicene) [ 27 , 28 ] or germanium (germanene) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for graphene and graphene oxide, its morphological characteristics have been exploited for the fabrication of gas sensors. MoS 2 opens the doors to the discovery and isolation of novel 2D nanostructures of sulphides and selenides, like WS 2 , WSe 2 , MoSe 2 and so forth [ 22 , 23 , 24 ]. On the other hand, 2D materials constituted of just one atomic species have been successfully synthesized [ 25 ], like one layer thick black phosphorus (phosphorene) [ 21 , 26 ] or silicon (silicene) [ 27 , 28 ] or germanium (germanene) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bulk TMDs can therefore be exfoliated to single or few layers. The isolation of a suspended MoS 2 monolayer was first achieved in 1986 . This was driven by the discovery of graphene in 2004 by Novoselov and Geim after which our curiosity to find other single atom and single unit cell thick two-dimensional (2D) materials started in earnest. Since then, the level of interest in TMDs has grown massively for both fundamental studies as well as their significant promise in numerous application areas such as microelectronics, , batteries, solar cells, , sensors, and biomedicine. TMDs comprise a metal layer sandwiched between two chalcogen layers . As illustrated in Figure a, the plane containing the metal atoms is located between two planes of chalcogen atoms, forming a hexagonal arrangement, which can be trigonal prismatic or octahedral.…”
mentioning
confidence: 99%
“…This is the principle of its application in gas sensors [11,12]. Among transition metal sulfides, molybdenum disulfide (MoS 2 ) is the earliest and most widely studied material [13][14]. A large number of previous experiments have shown that MoS 2 is an ideal transition metal sulfide that can be used as a gas-sensing material for chemical sensors [15][16][17].…”
Section: Introductionmentioning
confidence: 99%